Heterocyclic bibenzimidazole derivatives as topoisomerase I inhibitors - Jin, S.; Kim, J.S.; Sim, S.P; Liu, A.; Pilch, D.S.; Liu, L.F.; LaVoie, E.J. (Bioorganic & Medicinal Chemistry Letters, 2000)
A series of 2′-heterocyclic derivatives of 5-phenyl-2,5′-1H-bibenzimidazoles were evaluated for topoisomerase I poisoning activity and cytotoxicity. Topo I poisoning activity was associated with 2′-derivatives that possessed a hydrogen atom capable of hydrogen bond formation, suggesting that the interatomic distances between such hydrogen atoms and the heteroatoms on the adjacent benzimidazole influence activity.